2007
DOI: 10.1111/j.1556-4029.2007.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Malingered PTSD: An Overview of Clinical, Psychometric, and Physiological Assessment: Where Do We Stand?

Abstract: Posttraumatic stress disorder (PTSD) is a condition that can be easily malingered for secondary gain. For this reason, it is important for physicians to understand the phenomenology of true PTSD and indicators that suggest an individual is malingering. This paper reviews the prevalence of PTSD for both the general population and for specific events, such as rape and terrorism, to familiarize evaluators with the frequency of its occurrence. The diagnostic criteria for PTSD, as well as potential ambiguities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 108 publications
(134 reference statements)
0
32
0
Order By: Relevance
“…A substantial literature exists regarding interview strategies for detecting feigning or malingering, particularly when it comes to PTSD cases (Hall & Hall, 2007;Guriel & Fremouw, 2003;Resnick, West, & Payne, 2008;Taylor, Frueh, & Asmundson, 2007;Knoll & Resnick, 2006;Rogers, 2008;Simon, 2003). We highly recommend that the reader consult the aforementioned references for detailed guidance, but some general interview guidelines from this literature include the following:…”
Section: Screening and Assessment For Exaggeration And Feigning: Intementioning
confidence: 97%
“…A substantial literature exists regarding interview strategies for detecting feigning or malingering, particularly when it comes to PTSD cases (Hall & Hall, 2007;Guriel & Fremouw, 2003;Resnick, West, & Payne, 2008;Taylor, Frueh, & Asmundson, 2007;Knoll & Resnick, 2006;Rogers, 2008;Simon, 2003). We highly recommend that the reader consult the aforementioned references for detailed guidance, but some general interview guidelines from this literature include the following:…”
Section: Screening and Assessment For Exaggeration And Feigning: Intementioning
confidence: 97%
“…Another limitation of this work is that we did not address the issue of malingering, which has been identified as a challenge in assessing PTSD, especially when benefits may be at stake (Hall & Hall, 2007). Concerns about losing benefits may motivate some individuals to feign PTSD symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Research has consistently indicated the ease at which PTSD can be simulated (Guriel & Fremouw, 2003;Hall & Hall, 2007, Taylor, Frueh & Asmundson, 2007Sullivan & King 2010) and the majority of research investigating malingering utilises PTSD as the illness that is simulated. The findings of the present study raise the suggestion that the issue of malingering should not be examined exclusively using PTSD as the findings imply that malingering in the context of RTA claims may not be bound by any one complaint.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, research to date has focused mainly on malingered PTSD, and what is apparent is that due to the subjective nature of PTSD symptoms the illness can be easily malingered 2007;Guriel & Fremouw, 2003), with some researchers concluding: 'there is no one way to identify the malingering of PTSD' and 'it is critical to examine multiple sources of data and to use sound clinical judgement' (Hall & Hall, 2007). Consequently, this is a further area which complicates the assessment of malingering and this paper by no means is a gibe on how forensic mental health assessments are undertaken, it is more the aim to highlight to the reader the difficult task faced by professionals.…”
Section: Detecting Malingeringmentioning
confidence: 99%